Phenotypic Definition of Effector and Memory T-Lymphocyte Subsets in Mice Chronically Infected with Mycobacterium tuberculosis - Henao-Tamayo, Marcela I. (American Society for Microbiology (ASM), 2010)
The bacterium Mycobacterium tuberculosis remains one of the world's most successful pathogens, a situation that is aggravated by the fact that the existing vaccine, Mycobacterium bovis BCG, is not effective in adults. As with any vaccine, the purpose of giving BCG vaccination is to establish a long-lived state of memory immunity, but whether this is successfully completely established is still unclear. It is generally accepted that memory T cells can be divided into central and effector memory populations by function and by phenotype; however, the majority of data supporting this division have been generated using transgenic mouse models or mice that have recovered from acute viral infections. Tuberculosis, on the other hand, represents a persistent, chronic state of immunity in which the presence of memory T cells is far less well defined. We show here that mice vaccinated with BCG or chronically infected with M. tuberculosis establish antigen-specific populations of cells within the lungs that predominantly express a cellular phenotype consistent with their being effector or effector memory cells. In contrast, cells with a central memory phenotype exist in much lower numbers in the lungs but can be found in significantly larger numbers in the spleen, where they may represent a potential reservoir. These data suggest that the effector-to-central-memory T-cell transition may well be minimal in these persisting mycobacterial infections, and they support a novel hypothesis that this may explain the fundamental basis of the failure of the BCG vaccine in humans.